Pregnancy‐Related Risk Factors Are Associated With a Significant Burden of Treated Hypertension Within 10 Years of Delivery: Findings From a Population‐Based Norwegian Cohort - Grace M. Egeland (Wiley, 2018)
BackgroundThe association between pregnancy complications and women's later cardiovascular disease has, primarily, been evaluated in studies lacking information on important covariates. This report evaluates the prospective associations between pregnancy‐related risk factors (preeclampsia/eclampsia, gestational hypertension, pregestational and gestational diabetes mellitus, preterm delivery, and fetal growth restriction) and pharmacologically treated hypertension within 10 years after pregnancy, while adjusting for a wide range of covariates. Methods and ResultsPrepregnancy normotensive women participating in the MoBa (Norwegian Mother and Child Cohort Study) from January 2004 through July 2009 were linked to the Norwegian Prescription Database to identify women with pharmacologically treated hypertension beyond the postpartum period of 3 months. The burden of hypertension associated with pregnancy‐related risk factors was evaluated using an attributable fraction method. A total of 1480 women developed pharmacologically treated hypertension within the follow‐up among 60 027 women (rate of hypertension, 3.6/1000 person‐years). The proportion of hypertension associated with a history of preeclampsia/eclampsia, gestational hypertension, preterm delivery, and pregestational or gestational diabetes mellitus was 28.6% (95% confidence interval, 25.5%–31.6%) on the basis of multivariable analyses adjusting for numerous covariates. The proportion was similar for women with a healthy prepregnancy body mass index (18.5‐24.9 kg/m2; attributable fraction (AF)% 25.9%; 95% confidence interval, 21.3%‐30.3%), but considerably higher for nulliparous women at baseline within the first 5 years of follow‐up. Small‐for‐gestational age, however, did not increase subsequent hypertension risk in multivariable analyses. ConclusionsA structured postpartum follow‐up of high‐risk women identified through pregnancy‐related risk factors would facilitate personalized preventive strategies to postpone or avoid onset of premature cardiovascular events.